2012
DOI: 10.1093/toxsci/kfs015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tris(1,3-dichloro-2-propyl) phosphate and Tris(1-chloropropyl) phosphate on Cytotoxicity and mRNA Expression in Primary Cultures of Avian Hepatocytes and Neuronal Cells

Abstract: Tris(1,3-dichloro-2-propyl) phosphate (TDCPP) and tris(1-chloropropyl) phosphate (TCPP) belong to a group of chemicals collectively known as triester organophosphate flame retardants (OPFRs). OPFRs are used in a wide range of consumer products and have been detected in biota, including free-living avian species; however, data on toxicological and molecular effects of exposure are limited. An in vitro screening approach was used to compare concentration-dependent effects of TDCPP and TCPP on cytotoxicity and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 39 publications
5
104
1
Order By: Relevance
“…Liu et al (2013a) evaluated the effects of TDCPP and TPP on six receptor-associated expression of mRNA in zebrafish embryos/ larvae, and the results showed that TH receptor-centered gene networks were altered by OPEs. Using real-time reverse transcription-PCR, it has been demonstrated that exposure to TDCPP and TCPP altered the mRNA abundance of genes associated with the TR pathway in cultured hepatocytes and neuronal cells derived from embryonic chickens (Crump et al, 2012;Farhat et al, 2013). According to the results of previous studies, TR pathway appears to be interfered by OPEs.…”
Section: J O U R N a L O F E N V I R O N M E N T A L S C I E N C E Smentioning
confidence: 94%
“…Liu et al (2013a) evaluated the effects of TDCPP and TPP on six receptor-associated expression of mRNA in zebrafish embryos/ larvae, and the results showed that TH receptor-centered gene networks were altered by OPEs. Using real-time reverse transcription-PCR, it has been demonstrated that exposure to TDCPP and TCPP altered the mRNA abundance of genes associated with the TR pathway in cultured hepatocytes and neuronal cells derived from embryonic chickens (Crump et al, 2012;Farhat et al, 2013). According to the results of previous studies, TR pathway appears to be interfered by OPEs.…”
Section: J O U R N a L O F E N V I R O N M E N T A L S C I E N C E Smentioning
confidence: 94%
“…However, because of the large time span and the limited magnitude of the reviewed studies, we cannot determine clear differences of OPFRs metabolites rates among individuals, sexes and species. Crump et al (2012) have mentioned that some metabolites of OPFRs are comparatively more stable than their parent compounds in the body; hence, some of the adverse effects of OPFRs may, in fact, be the result of their metabolites. Meeker et al (2013a) reported a significant or suggestive relationship between two urinary OPFR metabolites (BDCIPP and DPHP) and serum hormone levels in men.…”
Section: Kinetics Of Metabolismmentioning
confidence: 99%
“…Liu et al (2012) demonstrated that treatment with TDCPP upregulated mRNA expression associated with steroidogenesis, downregulated mRNA expression of two sulfotransferase genes, and increased testosterone (T) and 17␤-estradiol (E2) productions in H295R cells and in zebrafish. Furthermore, results of epidemiological and controlled laboratory studies suggested that TDCPP affects the thyroid endocrine system and alters development-related mRNA expression (Crump et al, 2012;Liu et al, submitted for publication;Meeker and Stapleton, 2010). For example, Meeker and Stapleton (2010) reported that increased concentrations of TDCPP in house dust were associated with decreased concentrations of free thyroxin (T4) in the serum of adult men.…”
Section: Introductionmentioning
confidence: 99%